TANTANGAN DAN SOLUSI TERHADAP KETIMPANGAN AKSES PENDIDIKAN DAN LAYANAN KESEHATAN YANG MEMADAI DI TENGAH PANDEMI COVID-19 - Fitri, Winda; Octaria, Melvina; Irvanaries, Irvanaries; Suwanny, Novy; Sisilia, Sisilia; Firnando, Firnando (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
The widespread use of COVID-19 causes trouble to many sectors in the daily life of many people, in many public sectors. Education platforms are forced to go online, despite the lack of access towards the internet. Moreover, problems such as the demand to provide access for practical work to boost the performance of Sustainable Development Goals needs a lot of adjustment. Aside to that, healthcare also faces the same problem. Status quo shows that access to healthcare isn’t yet feasible for everyone as there are still many districts left with none. Other problems that occur are such as the lack of provided facilities to support healthcare. With this being said, the goal to provide healthcare will never be achieved as healthcare facilities will be demanded to be utilized to fight and handle Victims of COVID-19. This forces the society to do a major change in daily life activities, such as to apply social distancing, wearing maskers, and apply the given safety protocol